Free independent travellers (FIT) outbound travel intention post-COVID-19: integrating the theory of planned behaviour with perceived risk / Nhajril Kamaruddin - Kamaruddin, Nhajril (2024)
This study conceptualises the Theory of Planned Behaviour elements (attitude, subjective norms, perceived behaviour control, behavioural intention) with interpandemic perceived risk dimension (COVID-19 risk and transmission risk) in an integrated framework. The study examines the impact of COVID-19 perceived risk towards Malaysian free independent travellers (FIT) post-pandemic outbound travel behaviour. The study also investigates whether travel attitudes mediate between tourists' inter-pandemic perceived risk and post-pandemic outbound travel intentions. The study employed a non-probability purposive sampling method, collecting data from 345 respondents via social media platforms. Partial Least-squares-Structural Equation Modelling (PLS-SEM) was employed to analyse the data and identify key factors affecting post-pandemic travel intentions. The results indicate an insignificant causal relation between the COVID-19 perceived risk and FITs post-pandemic tourist attitude and travel intentions. Conversely, the study revealed significant relationships between post-pandemic outbound travel attitude and perceived behavioural control on travel intentions. However, subjective norms are not considered a significant factor influence travel intention. Furthermore, the research confirmed the mediating effect of travel attitude on the relationship between COVID-19 perceived risk (inter-pandemic COVID-19 risk and transmission risk perception) and outbound travel intentions. The study's findings reveal an interesting contradiction, as there is an insignificant causal relationship between COVID-19 perceived risk and FITs post-pandemic travel attitude and intentions. This divergence challenges conventional assumptions and warrants further exploration and understanding. The study contributes to the existing body of knowledge by highlighting this discrepancy. It encourages future research to delve deeper into the underlying factors influencing travellers' attitudes and intentions during the post-pandemic period. The study provides insights into the perceptions and intentions of Malaysian free independent travellers (FIT) specifically. Besides, the study comprehensively explains how perceived risk influences post-pandemic outbound travel behaviour. The mediating effect adds depth to understanding the relationship between perceived risk, travel attitude and intentions.